Association of social & psychological aspects of quality of life and educational level of patients with different orofacial cleft - Ahmed, Mahnoor Mansoor; Shahid, Nameeka; Mumtaz, Nazia; Ghulam Saqulain (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the social and psychological domains of quality of life of children with orofacial clefts in the context of different types of clefts and educational levels. Method: The cross-sectional study was conducted at Clapp Hospital and Mayo Hospital, Lahore, Pakistan from September 1, 2020, to January 3, 2021, and comprised subjects of either gender aged 6-18 years having orofacial clefts. Data was collected using the CLEFT-Questionnaire along with a basic demographic sheet. Data was analysed using SPSS 23. Results: Of the 80 subjects, 40(50%) each were males and females. The overall mean age was 12.41±3.39 years. A significant association of types of orofacial clefts with social function (p<0.05) and psychological function (p<0.05) was observed. The highest mean score of 27.89±3.41 and 26.11±1.76 was noted for unilateral left side cleft lip, and primary palate, respectively. No significant association of level of education with social function (p>0.05) and psychological function (p>0.05) was noted. Conclusion: Different types of orofacial clefts affected the psychological and social aspects of quality of life of patients differently, but the difference was not significantly correlated with the education level. Key Words: Cleft lip, Cleft palate, Cleft lip palate, Quality of life, Psychological, Social, Educational level.